Reliability of artificial intelligence in civilian and military applications - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose The goal of this paper is to show the importance of reliability and availability for artificial intelligence (AI), which is in nowadays applying in almost every area of human life, civilian or military. Everything can fail, and AI is not an exception, as any other product or device. AI also need to be reliable. Artificial intelligence is mainly realized as software, but it involves hardware, data and human, so it is complex for building in and assessing reliability.Methods: This research is done using published articles by the author of this work, and some other papers and documents.Results: The result of this research is the brief definitions of reliability, availability, artificial intelligence, reliability of hardware, software, data and human, reliability of AI, and brief analyse of some reasons for unreliability of AI, such as quality of data, small or insufficient number of training and test data, training on unreal data, nature of learning algorithms and user incompetence.Conclusion Reliability of artificial intelligence are very complex and very important, so it must be considered during the design and using.
Keywords: artificial intelligence, reliability, availability, hardware, software, human, data